Primary Duodenal Mucosa-Associated Lymphoid Tissue (Malt) Lymphoma – a Rare Presentation of Gastric Outlet Obstruction. (2007) - Tadmor, Tamar; Rainis, Tova; Bejar, Jacob; Attias, Dina; Lavy, Alexandra
Abstract : Malignant lymphoma of mucosa-associated lymphoid tissue (MALT) can arise in a variety of anatomical sites. The majority of these tumors arise in the stomach, with fewer than 30% arising in the small intestine. Primary duodenal MALT lymphoma is a very rare neoplasm. There are very few cases of duodenal MALT lymphoma reported in the literature. This is the third published case presenting clinically as a gastric outlet obstruction. The patient was successfully treated with a combination of chemotherapy and rituximab.